Can read, will read four-pronged approach to the teaching of beginning reading - Padilla, Portia P.; Alfonso, Grace Javier 1950- (U.P. Open University, 2004)
Development of the four-pronged approach in teaching beginning reading, as Teacher Yvette Concepcion-Alcazar demonstrates this method upon her Kinder-Sampaguita class of the U.P. Integrated School (UPIS).